Synthesis of lipids and N-containing molecules 1 - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Fatty acid synthase complex in detail, Fatty acid biosynthesis and its regulation, Biosynthesis of complex lipids, Synthesis of fats and phospholipids
Reviewed at 2022/11/27